2014
DOI: 10.1017/s0001924000009337
|View full text |Cite
|
Sign up to set email alerts
|

On power and actuation requirement in swashplateless primary control of helicopters using trailing-edge flaps

Abstract: This paper examines three specific aspects pertaining to the trailing-edge flap (TEF) enabled swashplateless primary control of a helicopter. The study is based on a utility helicopter very similar to the UH-60A Blackhawk helicopter, with rotor torsion frequency reduced to 2•1/rev, and 20% chord TEFs extending from 70-90% span. The questions addressed in the paper are the power penalty due to aerodynamic drag associated with TEF control, the pitch-index required to limit the range of TEF deflections over varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…Figure 1a and 1b show respectively the power and collective pitch requirements to trim the rotor at sea-level. It can be seen that power reduction is mainly linked to the rotor RPM and are according to the studies found in literature [15,26]. It is also observed that slowing the rotor has more influence than camber morphing.…”
Section: Significance Of Passive Morphing With Vsrsupporting
confidence: 73%
“…Figure 1a and 1b show respectively the power and collective pitch requirements to trim the rotor at sea-level. It can be seen that power reduction is mainly linked to the rotor RPM and are according to the studies found in literature [15,26]. It is also observed that slowing the rotor has more influence than camber morphing.…”
Section: Significance Of Passive Morphing With Vsrsupporting
confidence: 73%